Bridge Condition Assessment (Case Study: Padang – Bukittinggi Route) - Amelia Masza; Benny Hidayat; Taufika Ophiyandri (Universitas Negeri Padang, 2025)
Bridges are critical components of transportation infrastructure, ensuring smooth traffic flow and regional connectivity. However, their structural conditions are influenced by various factors, including traffic loads, material durability, and natural disasters such as earthquakes and floods. Despite existing bridge maintenance frameworks, a comprehensive condition assessment specifically tailored to the Padang-Bukittinggi route has not been thoroughly conducted. This study introduces a systematic evaluation using the Bridge Condition Rate (BCR) method to provide data-driven maintenance recommendations. A total of eight bridges along the Padang-Bukittinggi route were assessed through detailed and routine inspections, followed by cross-case analysis. The results indicate that 75% of the bridges (6 out of 8) require periodic maintenance (BCR=2), 12.5% (1 bridge) necessitates rehabilitation (BCR=3), and another 12.5% (1 bridge) demands immediate replacement (BCR=5) due to severe structural damage. These findings highlight the urgency of targeted maintenance strategies to enhance bridge longevity and operational safety. The study provides critical insights for policymakers and infrastructure authorities, emphasizing the need for proactive maintenance planning to ensure road network sustainability and public safety.